ISOLASI DAN SKRINING MOLEKULER BAKTERI ASAM LAKTAT PEMBAWA GEN GLUKANSUKRASE DARI MAKANAN DAN MINUMAN MENGANDUNG GULA (Makara Journal of Science, 2010)
Isolation and Molecular Screening of Glucansucrase Gene Harboring-Lactic Acid Bacteria. Exopolysaccharides (EPS) have been possessed to be used in pharmaceutical, cosmetic and food industries. Lactic acid bacteria (LAB) produce a wide variety of exopolysaccharides and carries sucrase genes glucansucrase/glucosyltransferase (gtf) and fructansucrase/fructosyltransferases (ftf) for EPS production. In this study, the isolation and screening of EPS producing-LAB (EPS-LAB) were carried out on modified de Mann-Rogosa-Sharpe (MRS) agar medium supplemented with 10% of sucrose on LAB isolated from various unique sugar containing-foods and -beverages originated from local sources. Besides obtaining EPS-LAB, this study aimed to screen for gtf gene as well as to molecular identify strains by using PCR technique. Degenerate primer pairs DegFor and DegRev which targeted the conserved region of gtf genes catalytic domain were used, whereas LABfw and LABrv were used to molecular identify strains using 16S rRNA gene. An approximately 660 base pairs (bp) amplicons which targeted gtf gene were obtained from 13 out of 16 srains chosen. Result from PCR of 16S rRNA gene identification on gtf positive strains revealed that all strains were molecular identified as LAB after DNA sequencing analysis by using blastn. A rare EPS-producing LAB were obtain i.e. Weissella. Strains obtained in this study are potential sources for exploring novel sucrase gene/s and obtain unique EPS polymer product/s.